Changes in consumption of opioid analgesics in Israel 2009 to 2016: An update focusing on oxycodone and fentanyl formulations. Issue 5 (28th February 2018) - Ponizovsky, Alexander M.; Marom, Eli; Weizman, Abraham; Schwartzberg, Eyal
Abstract: Purpose: The purpose of the study is to assess opioid (morphine, methadone, oxycodone, pethidine, and fentanyl) consumption in Israel during 2009 to 2016 and identify recent trends. Methods: Data for all treatment settings, private and public, for the years 2009 to 2016, were extracted from the Israel Ministry of Health's Pharmaceutical Administration database. The data were used to calculate defined daily doses (DDD) per 1000 inhabitants per day, of the various drugs. Results: Consumption of the 5 opioids increased by 68%, from 3.40 DDD/1000 inhabitants/day in 2009 to 5.72 DDD/1000 inhabitants/day in 2016. This trend resulted mostly from increases in oxycodone consumption from 0.50 DDD/1000 inhabitants/day to 2.03 DDD/1000 inhabitants/day (namely, 4‐fold) and in fentanyl consumption, from 1.09 DDD/1000 inhabitants/day to 2.33 DDD/1000 inhabitants/day (about 2‐fold). The use of the 3 remaining opioids decreased substantially as follows: pethidine from 0.03 DDD/1000/day in 2009 to 0.007 DDD/1000 inhabitants/day in 2016 (−67%), methadone from 1.61 DDD/1000 inhabitants/day to 1.20 DDD/1000 inhabitants/day (−25%), and morphine from 0.17 DDD/1000 inhabitants/day to 0.15 DDD/1000 inhabitants/day (−12%). An increasing trend was also observed in the use of oxycodone/naloxone (Targin) and oxycodone/acetaminophen (Percocet) combinations, while a decrease was observed in the use of pure oxycodone formulations. Conclusions: The increase in opioid consumption persisted throughout the years 2009 to 2016. This has been associated with substantial changes in the patterns of prescribing opioids, characterized by increases in oxycodone and fentanyl prescriptions and decreases in morphine, methadone, and pethidine prescriptions. A national program aiming to ensure safe use of opioids in the treatment of chronic pain is warranted.